الجريدة الرسمية العدد 13 مكرر (و) - جمهورية مصر العربية (المطابع الأميرية, 2025)
قرارات رئيس مجلس الوزراء: قرار رقم 730 لسنة 2021 // قرار رقم 731 لسنة 2021 // قرار رقم 732 لسنة 2021 // قرار رقم 733 لسنة 2021 // قرار رقم 734 لسنة 2021